2009
DOI: 10.1111/j.1750-3841.2009.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Properties of Fermented Soy and Dairy Milks Prepared with Lactic Acid Bacteria

Abstract: Fermented soy and dairy milk preparations provide a means for delivering lactic acid bacteria and their fermentation products into the diet. Our aims were to test immunomodulatory bioactivity of fermented soy beverage (SB) and dairy milk blend (MB) preparations on human intestinal epithelial cells (IEC) and to determine the impact of freezing medium on culture survival prior to bioactivity analyses. Fermented SB and MB were prepared using pure or mixed cultures of Streptococcus thermophilus ST5, Bifidobacteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 42 publications
1
36
0
2
Order By: Relevance
“…Other activities have been widely studied on HT29 cells or derived lines, such as immunomodulatory, antioxidant or barrier protective properties. For instance, milk and soy ferments with different strains of lactic acid bacteria (LAB) were evaluated on human intestinal epithelial cells, including HT29 cells, to test their immunomodulatory activity (Wagar et al 2009 ). The study was carried out on cells treated with TNF-α and the production of IL-8 was evaluated in the cell supernatant by a commercial enzyme-linked immunosorbent assay.…”
Section: Functionality Studiesmentioning
confidence: 99%
“…Other activities have been widely studied on HT29 cells or derived lines, such as immunomodulatory, antioxidant or barrier protective properties. For instance, milk and soy ferments with different strains of lactic acid bacteria (LAB) were evaluated on human intestinal epithelial cells, including HT29 cells, to test their immunomodulatory activity (Wagar et al 2009 ). The study was carried out on cells treated with TNF-α and the production of IL-8 was evaluated in the cell supernatant by a commercial enzyme-linked immunosorbent assay.…”
Section: Functionality Studiesmentioning
confidence: 99%
“…In addition to these ferment preparations, an unfermented SM and MB control and a lactic acid acidified (pH of 4.70 ± 0.1) SM and MB control was included as well. Cultures and controls were incubated at 37°C until a pH of 4.70 ± 0.1 was reached for a maximum of 24 h. Ferments and controls were frozen and maintained at −80°C as previously described (Wagar et al, 2009). The effects of ferment medium on bacterial culture viability in both soy and milk ferments were previously reported and both R0175 and R0052 showed comparable growth rates in both ferment substrates (Wagar et al, 2009).…”
Section: Ferment Preparationmentioning
confidence: 99%
“…Therefore, fermented soy milk offers many nutritional benefits. Previously, soy milk and dairy milk fermented with Streptococcus thermophilus ST5 in combination with Bifidobacterium longum R0175 has been down to down-regulate IL-8 production by HT-29 intestinal epithelial cells (Wagar, Champagne, Buckley, Raymond, & Green-Johnson, 2009) and have previously shown the potential to modulate the immune system (Easo et al 2002;Wallace, Bradley, Buckley, & Green-Johnson, 2003;Wood, Keeling, Bradley, JohnsonGreen, & Green-Johnson, 2007), prevent infection (Johnson-Henry et al 2004;Johnson-Henry et al, 2005), reduce symptoms of stress (Gareau, Jury, MacQueen, Sherman, & Perdue, 2007;Zareie et al, 2006) and produce bioactive compounds (Fiander, Bradley, Johnson-Green, & Green-Johnson, 2005). TGF-β1 is a key immunoregulatory cytokine and can also influence cell proliferation and differentiation, as well as other functions depending on cell type, and is also considered an immunoregulatory cytokine.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that of L. helveticus R0052 reduces IL-1, IL-6 but not significantly TNF- (Cazzola et al 2010) whereas B. longum R0175 can reduce IL-8 and TNF- (Wagar et al 2009) indicating that each strain has a specific effect on pro-inflammatory cytokines synthesis while they possibly are ineffective against stress (Diop et al 2008;Girard et al 2009;Messaoudi et al). We combined both strains and found significant therapeutic effects on post-MI behavior, including behavioral despair (Forced swim test), passive avoidance and socialization Arseneault-Bréard et al 2011).…”
Section: Probioticsmentioning
confidence: 99%